Edukasi dan Pelatihan Menstrual Hyegine Management pada Remaja Putri - Ritawati; Asniah Syamsuddin; Latifah Hanum; Supriyanti; Nurhayati (JKA, 2024)
Menstrual Hygiene Management (MKM) or better known as "Menstrual Hygiene Management" (MHM) is very important to understand the context and urgency of this topic. Menstrual Hygiene Management or what we call Menstrual Hygiene Management (MKM) was initiated by a non-governmental organization in Germany, Wash United in 2013 and was first celebrated on May 28 2014. The 28th was taken as a symbol of menstruation in Indonesia and was celebrated on May 28 2017 by the AMPL Network (Drinking Water and Environmental Health). The target of MKM is teenagers. This is because in the UKS framework, teenagers are part of the UKS targets. Through this Community Service (PKM) activity, it is hoped that it can provide education and good hygiene management related to menstrual hygiene in teenagers. Through this service activity, it is hoped that it can open useful insights and knowledge related to Menstruation or its Management (MKM). It is the management of hygiene and health when women experience menstruation. The conclusion that can be drawn from this activity is that based on the results of the presentation at International PKM activities, it can provide education and understanding of procedures for maintaining menstrual hygiene. This activity can also be used as a reference by every teenager who experiences menstruation. MHM also has a very important role in maintaining cleanliness and managing hygiene when menstruation occurs. This international PKM activity is of special concern for every teenager to be able to participate and carry out